Tourism development of waterfalls and waterfalls in the Kurdistan Region – Iraq: (Kani Best waterfall as a model) - Rashid, Shirwan; Al-Safar, Bahri (Al-Adab Journal, 2022)
This study aims to highlight the importance and role of waterfalls and waterfalls in the Kurdistan Region - Iraq and their uses in the fields of tourism activity. And employed to develop tourism in the study area. For the purpose of reaching the main objectives and investigating its hypothesis, the research is divided into three axes: The first axis dealt with the definition of the study area and its subjects, The second axis then dealt with the current reality of waterfalls and waterfalls in the study area, While the third axis dealt with the tourism development of Kani Best Falls. In the end, the research concluded that waterfalls and waterfalls as well as water sources are an important and influential factor in the emergence of tourist areas in the study area. This is in addition to a number of other natural and human factors that also contribute to a prominent role in creating tourist areas, which paves the way for tourists to practice their tourist activity associated with the presence of water bodies such as swimming and the practice of driving boats and enjoy the natural scenery in the study area.